A novel anticonvulsant modulates voltage‐gated sodium channel inactivation and prevents kindling‐induced seizures. (22nd July 2013) - Ashraf, Muhammad N.; Gavrilovici, Cezar; Ali Shah, Syed U.; Shaheen, Farzana; Choudhary, Muhammad I.; Rahman, Atta‐ur; Fahnestock, Margaret; Simjee, Shabana U.; Poulter, Michael O.
Abstract Here, we explore the mechanism of action of isoxylitone (ISOX), a molecule discovered in the plant Delphinium denudatum, which has been shown to have anticonvulsant properties. Patch‐clamp electrophysiology assayed the activity of ISOX on voltage‐gated sodium channels (VGSCs) in both cultured neurons and brain slices isolated from controls and rats with experimental epilepsy (kindling model). Quantitative transcription polymerase chain reaction (qRT‐PCR) (QPCR) assessed brain‐derived neurotrophic factor (BDNF) mRNA expression in kindled rats, and kindled rats treated with ISOX. ISOX suppressed sodium current (INa) showing an IC50 value of 185 nM in cultured neurons. ISOX significantly slowed the recovery from inactivation (ISOX τ = 18.7 ms; Control τ = 9.4 ms; p < 0.001). ISOX also enhanced the development of inactivation by shifting the Boltzmann curve to more hyperpolarized potentials by −11.2 mV (p < 0.05). In naive and electrically kindled cortical neurons, the IC50 for sodium current block was identical to that found in cultured neurons. ISOX prevented kindled stage 5 seizures and decreased the enhanced BDNF mRNA expression that is normally associated with kindling (p < 0.05). Overall, our data show that ISOX is a potent inhibitor of VGSCs that stabilizes steady‐state inactivation while slowing recovery and enhancing inactivation development. Like many other sodium channel blocker anti‐epileptic drugs, the suppression of BDNF mRNA expression that usually occurs with kindling is likely a secondary outcome that nevertheless would suppress epileptogenesis. These data show a new class of anti‐seizure compound that inhibits sodium channel function and prevents the development of epileptic seizures. <boxed-text content-type="graphic" id="jnc12352-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Isoxylitones, isolated from Delphinium denudatum root prevent seizure induction. Activity was tested on voltage‐gated sodium channels (VGSCs) in both cultured neurons and brain slices isolated from controls and rats with experimental epilepsy (kindling model). Isoxylitones enhanced sodium channel inactivation with an IC50 of about 200 nM. Our findings suggest isoxylitones as a potential novel anticonvulsant agent.